2023
DOI: 10.3389/fimmu.2023.1132692
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: ICIs-induced Guillain–Barré syndrome recovered from mycophenolate mofetil

Abstract: The emergence of immune checkpoint inhibitors (ICIs) has significantly prolonged the survival time of cancer patients. However, it may also lead to various immune-related adverse events (irAEs), including Guillain–Barré syndrome (GBS), a rare type of irAE. Most GBS patients can recover spontaneously due to the self-limited nature of the disease, but severe cases can result in respiratory failure or even death. Here we report a rare case of GBS occurring in a 58-year-old male patient with non-small cell lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Both types of drugs have the potential to induce GBS ( 9 ). In similar instances, the patients of Ding et al ( 10 ) and Manam et al ( 11 ) were also treated with a combination of chemotherapy and ICIs. Both authors considered GBS as a possible result of ICIs.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Both types of drugs have the potential to induce GBS ( 9 ). In similar instances, the patients of Ding et al ( 10 ) and Manam et al ( 11 ) were also treated with a combination of chemotherapy and ICIs. Both authors considered GBS as a possible result of ICIs.…”
Section: Discussionmentioning
confidence: 95%
“…Apart from GBS, antineoplastic chemotherapeutic agents can directly induce neurotoxicity and lead to chemotherapy-induced peripheral neuropathy (CIPN). It has been demonstrated that immune checkpoint inhibitors are associated with a higher risk of neurological adverse events compared to control groups, yet this risk is significantly lower when compared to chemotherapeutic agents ( 10 , 12 ). Both conditions have comparable clinical symptoms, which may lead to weakness and numbness in the limbs, as well as sensory abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma exchange (PE) can be used as a second-line treatment if previous treatments are ineffective. However, the efficacy of plasmapheresis as a first-line treatment is unknown [ 29 ]. One case report in the literature reports improvement in ICIs-induced GBS with the use of mycophenolate mofetil [ 29 ].…”
Section: Discussionmentioning
confidence: 99%